2011
DOI: 10.1007/s10384-011-0035-1
|View full text |Cite
|
Sign up to set email alerts
|

Suprachoroidal implant surgery in intractable glaucoma

Abstract: Drainage of the aqueous humor from the anterior chamber to the suprachoroidal space via implantation of a modified silicone implant is effective in lowering the IOP in intractable glaucoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Laser goniopuncture[12] and newer goniosurgical procedures [e.g., trabecular microbypass (iStent),[13] trabectome microelectrocautery,[14] the Eyepass implant,[15] and canaloplasty[16] have been used to enhance conventional outflow pathways. Surgical procedures to augment suprachoroidal outflow include cyclodialysis,[17] suprachoroidal implants,[181920] seton devices,[21] and GMS placement in the suprachoroidal space. [1022] Studies have shown better safety profiles and similar short-term efficacy with these techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser goniopuncture[12] and newer goniosurgical procedures [e.g., trabecular microbypass (iStent),[13] trabectome microelectrocautery,[14] the Eyepass implant,[15] and canaloplasty[16] have been used to enhance conventional outflow pathways. Surgical procedures to augment suprachoroidal outflow include cyclodialysis,[17] suprachoroidal implants,[181920] seton devices,[21] and GMS placement in the suprachoroidal space. [1022] Studies have shown better safety profiles and similar short-term efficacy with these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that fibrosis can cause suprachoroidal devices to gradually fail. [2324] Although there has been some success with suprachoroidal tube implantation,[1819202125] a gradual loss of efficacy may occur. [1819] In one study, ultrasound biomicroscopy revealed that some cases of shunt failure were caused by fibrotic obstruction of the posterior tube lumen.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In contrast to these ab interno procedures, the combined trabeculectomy-cyclodialysis aims to direct flow not only into the suprachoroidal space, but also into the Schlemm canal and the subconjunctival space under a tight scleral trapdoor similar to that used in a trabeculectomy. This pathway is the target for procedures using intraocular microstents.…”
mentioning
confidence: 99%